Dynamic modelling of pollution flashover on high voltage outdoor insulators - Ali Salem, Ali Ahmed (2020)
The high voltage outdoor insulators are one of the most important components in the electrical power transmission system. During its lifetime, insulators are exposed to several failures. For this reason, it is crucial to continuously monitor its condition and investigate insulator performance under varying degrees of contamination. In this work, new techniques have been used to diagnose insulators' conditions based on Fast Fourier Transformer (FFT) Analysis of the leakage current. FFT analysis is commonly employed to investigate insulator statements under varying degrees of contamination and wetting rate using harmonic components and phase-shift angle of leakage current. It can be noted that proposed techniques have shown high efficiency in evaluating insulator status. The increase in pollution levels on insulators surfaces has affected the performance of insulators which leads to the occurrence of flashover on the insulator surface. The investigations carried out to understand the performance of polluted insulators may be grouped into three categories: natural testing, artificial testing or laboratory testing, and mathematical models. However, the method of actual testing of insulators suffers from limitations, for example, it is uneconomical, highly time-consuming, and gives nonreproducible results. So, artificial testing (experiments) and mathematical models have been used to understand and predict pollution flashover voltages of polluted insulators. In this study, a new mathematical model, based on the dimensional analysis method (DAM), is proposed. This model is used to forecast the contamination flashover voltage gradient of insulators under varying contamination and wetting conditions when subjected to AC voltages. The arc constants have been extracted from the V-I characteristics curve to estimate the dimensional constant. The Artificial Neural Network (ANN) and Adaptive Network-Based Fuzzy Inference System (ANFIS) were utilised also for the prediction of the mathematical model. Also, in this study, an improved static and dynamic mathematical model of critical parameters of polluted insulators is proposed based on an extended equivalent electric-circuit model of a polluted insulator. The effect of arc length and resistance of the pollution layer on critical flashover voltage investigated using the (RLC) circuit model. Finally, the experimental test results validate the competency of the proposed dynamic model via accurate performance prediction of polluted insulators. There is a good agreement between the results of the experiments of polluted insulators obtained in the laboratory and values calculated from the developed model